Iliac vein stenting as a durable option for residual stenosis after catheter-directed thrombolysis and angioplasty of iliofemoral deep vein thrombosis secondary to May–Thurner syndrome. (August 2014) - Park, Jae Young; Ahn, Jong Hyuk; Jeon, Yong Sun; Cho, Soon Gu; Kim, Jang Yong; Hong, Kee Chun
Introduction: This study aims to evaluate the primary patency and clinical outcomes after stenting for residual iliac venous stenosis during catheter-directed thrombolysis treatment of acute iliofemoral deep vein thrombosis arising from May–Thurner syndome. Methods: A retrospective study was done for the all patients who underwent iliac vein stenting after catheter-directed thrombolysis treatment of acute iliofemoral deep vein thrombosis due to May–Thurner syndrome from January 2005 to April 2011 in Inha University Hospital. Patient information was assembled from the electronic medical records, imaging and interview. The patency of iliac vein stent was evaluated with serial computed tomography. Results: Fifty-one patients were enrolled. The median age was 70 years (range 44–86). There were 37 females (72.5%). The duration of symptoms of acute deep vein thrombosis before catheter-directed thrombolysis treatment was 6 days (median, range 1–33). Self-expanding stent was used for iliac vein stenting. Initial technical success rate was 94.1%. There were two complications (3.9%): an arteriovenous fistula formation in left popliteal area and a right inguinal hematoma. Mean follow-up was 15.6 months (range 6 days–80.8 months). Primary patency rate after iliac vein stenting was 95.8% at 6 months, 87.5% at 12 months and 84.3% at 24 months. Four patients had recurrent thrombotic occlusion (7.8%) during the follow-up. Conclusion: Iliac vein stenting showed good primary patency rate with few complications. Iliac vein stenting is a durable option for residual stenosis after catheter-directed thrombolysis treatment of acute deep vein thrombosis in May–Thurner syndrome.